The crisis of the modern worldview and the category of death (based on vedic philosophy) - Zholomanova, A.; Karipbayev В. (Eurasian Journal of Religious Studies, 2021)
The article examines common trends in the development of the civilization of consumption, which determine the essence of the crisis worldview, its role in society. The types of civilizational conformism, which is considered as the main tool of existing social institutions and individual individuals in achieving the ultimate goals of the consumer type of life, have been identified and studied. Such a vision is due to the materialistic concept, which makes the process of life itself meaningless, temporary achievements. Consumer philosophy generates an exploitative type of existence, the results of which are catastrophic for society, as they contribute to the degeneration of human values, the lack of spiritual guidelines. The aim of the study is to consider the topic of death through the analysis of ancient Indian philosophy as a factor contributing to the acquisition of a stable worldview position by modern society. The authors investigate the topic of death on the platform of ancient Puranic scriptures, the value of which lies in the possibility of gaining awareness, structuredness, clarity in understanding worldview guidelines, and finding true values ​​by society. The scientific approach is characterized by the study of the causes of the crisis of the world outlook in modern society, as well as the very phenomenon of death, as a sobering factor in understanding the mission of living one’s own life. The practical meaning of the article lies in encouraging the individual and society as a whole, to a conscious, meaningful life by addressing the taboo topic of death. Such approaches are characteristic of theological philosophy, in particular, for Christian thought, but there was no separate topic for a detailed study of the philosophical aspect of the phenomenon of death in conditions of worldview chaos, the loss of spiritual guidelines in society, which is characteristic of the modern world. Key words: ideological crisis, values, death, thanatology, spirituality